The Effect of the Problem Based Learning Model Using Wordwall on the Motivation and Learning Outcomes of Sciences in Grade V Elementary School - Sinta Medya Agustin; Muhammadi; Mutiara Felicita Amsal; Salmaini Syofian (Postgraduate, University of Mataram, 2025)
This study aims to analyze the effect of the Problem-Based Learning (PBL) model assisted by Wordwall on the motivation and learning outcomes of fifth-grade science students in elementary schools. The focus of the study is to determine the extent to which the problem-based learning model assisted by the Wordwall application affects students' motivation and learning outcomes. This study aims to provide practical recommendations for educators in designing more effective learning strategies, especially in the elementary school context. This study uses a quantitative method with a quasi-experimental method in the form of a pre-experimental with a one-group pretest-posttest design. The research sample consisted of only one class as the experimental class, namely class Va. Learning outcome test in the form of multiple-choice questions based on cognitive indicators. The results of the study showed that there was a significant increase in student motivation and learning outcomes after the application of the problem-based learning model assisted by the Wordwall application. The statistical test used a t-test in the form of a paired sample t-test. This proves that there is a significant difference between the motivation scores and student learning outcomes before and after the application of the Problem-Based Learning (PBL) model assisted by Wordwall. Thus, it can be concluded that the application of the Problem Based Learning (PBL) learning model assisted by the Wordwall application has a positive effect on increasing the motivation and learning outcomes of class Va students.